2012
DOI: 10.1364/oe.20.015008
|View full text |Cite
|
Sign up to set email alerts
|

Large aperture PPMgLN based high-power optical parametric oscillator at 38 µm pumped by a nanosecond linearly polarized fiber MOPA

Abstract: We report a large aperture PPMgLN based OPO generating 21W of average output power at a slope efficiency of 45%. The OPO is pumped with the output from a polarization maintaining Ytterbium doped fiber MOPA operating at 1060nm producing 20ns pulses at a repetition rate of 100kHz and an average output power of 58W (after the isolators). A maximum of 5.5W of optical power was recorded at the idler wavelength of 3.82µm without thermal roll-off. The pulse rise/fall time plays a significant role in the OPO conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…We believe that the major cause of the thermal effect is the idler absorption that is unavoidable while the back conversion could be alleviated by optimizing the signal reflectivity. To alleviate the thermal roll-off problem, larger pump beam diameter [10] as well as thermal compensation methods such as semi-external-cavity structured OPO [18] should be taken into consideration under higher pump power.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We believe that the major cause of the thermal effect is the idler absorption that is unavoidable while the back conversion could be alleviated by optimizing the signal reflectivity. To alleviate the thermal roll-off problem, larger pump beam diameter [10] as well as thermal compensation methods such as semi-external-cavity structured OPO [18] should be taken into consideration under higher pump power.…”
Section: Resultsmentioning
confidence: 99%
“…According to these requirements, fiber lasers are supposed to be the best candidates among all the OPO pump sources due to their compactness, robustness, excellent beam quality, and simple thermal management schemes [3]. Therefore, fiber-laser-pumped OPOs have been extensively investigated from continuous wave (CW) to ultrashort pulsed operation schemes [4][5][6][7][8][9][10][11][12][13]. Among all these pump sources, fiber lasers with tens to hundreds of nanoseconds are particularly useful in outdoor applications for both environmental monitoring and missile countermeasures because simple linear cavities are applicable to such pump sources converting the pump power to idler output efficiently during each pulse with peak power higher than the CW OPOs and dimensions smaller than the synchronously pumped OPOs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have spent much effort on generating a long wavelength, high repetition rate mid-IR laser in recent years. In [11] demonstrated a maximum average power of 5.5 W idler laser at the wavelength of 3.82 μm at 100 kHz with the efficiency of 9.48%. In 2013, Chen et al [12] reported an idler laser at 3.82 μm with an average output power of 3.27 W under the pump power of 25 W at 65 kHz.…”
Section: Introductionmentioning
confidence: 99%